Wine tourism: Constructs of the experience - Madeira, A.; Correia, A.; Filipe, J. (Trends in tourist behavior: new products and experiences from Europe, 2019)
Wine tourism experiences include activities such as visits to wine routes and wine tastings and gastronomy in the producers and local restaurants, as well as ludic and cultural activities. This experience presupposes the interaction of tourists with their hosts and with the place as well as with the product (wine and food). This relation within hosts, guests and place have been applied and explored in a number of fields, however in terms of tourism the number of researches in this framework are scarce and it is even scarce in what refers to wine tourism. Theoretically supported by Pine and Gilmore (1998) definition of tourism experience, this research mostly based on literature review, depicts the recurrent phases of a wine tourism experience, underlining its constructs. The main focus of this chapter is the wine tourism experience that the guest faces when getting into contact with the elements comprising the wine tourism product. This study is supported in three dimensions of inter-action that explain the experience: Guest, Host and Place. The guest relates with the place based on his/her perceived brand equity and brand image, the host providing a good service to the guest manifest in his/her satisfaction and loyalty, being those the most important determinants of wine experience. The concept and boundaries of the wine tourism experience need to be established in order to understand the guest's experiential priorities.